2015
DOI: 10.1097/dbp.0000000000000134
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Sleep Disorders From Preschool to First Grade and Their Bidirectional Relationship with Psychiatric Symptoms

Abstract: Objectives: To examine the prevalence and stability of DSM-4-defined sleep disorders from preschool to first grade and to explore the bidirectional relationship between sleep disorders and symptoms of psychiatric disorders. Method: All children born in 2003 or 2004 in Trondheim, Norway, who attended regular community health checkups for 4-year-olds, were invited to participate (97.2% attendance; 82.0% consent rate, n 5 2475) in this study. The authors recruited a screen-stratified subsample of 1250 children an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 41 publications
5
25
2
Order By: Relevance
“…There were consistently stronger correlations among sleep problems and emotional dysregulation at each point from 2 to 3 years for the ADHD group compared to the no ADHD group. These findings are in contrast to those of Steinsbekk and Wichstrom, 25 who found evidence of ADHD symptoms contributing to later sleep problems across 4 to 6 years of age, but no evidence for the reverse. 1,47,48 We found evidence of reciprocal relations among sleep problems and emotional regulation in children with ADHD, which is consistent with our previous work.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…There were consistently stronger correlations among sleep problems and emotional dysregulation at each point from 2 to 3 years for the ADHD group compared to the no ADHD group. These findings are in contrast to those of Steinsbekk and Wichstrom, 25 who found evidence of ADHD symptoms contributing to later sleep problems across 4 to 6 years of age, but no evidence for the reverse. 1,47,48 We found evidence of reciprocal relations among sleep problems and emotional regulation in children with ADHD, which is consistent with our previous work.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous research has found robust associations between sleep and the development of attentional and emotional self-regulation capacities, including executive functioning in children with 24,25 and without ADHD. [26][27][28] Recently, the longitudinal bidirectional relationship among sleep problems and emotional and attentional regulation across early childhood have been documented in a population sample, 6 with the findings suggesting that sleep problems are a key early antecedent of later self-regulation problems.…”
mentioning
confidence: 96%
“…Seizures and sleep deprivation can exacerbate the presence of each other, thus creating a negative feed‐forward cycle . Moreover, studies report that more severe sleep deficiency is associated with greater degree of cognitive impairment, arrhythmias, and seizure severity . Here, we found that after epilepsy onset, young KO mice rest for similar amounts of time as WT mice.…”
Section: Discussionsupporting
confidence: 50%
“…Individuals (with and without epilepsy) who suffer from chronic sleep deficiency are more likely to experience cognitive impairments, cardiac arrhythmias, and apnea and to have shorter lifespans . There is a higher risk of premature mortality in epilepsy than the general population, with the incidence rate of sudden unexpected death in epilepsy (SUDEP) approximating 1 in 1000 cases every year .…”
Section: Introductionmentioning
confidence: 99%
“…Touchette et al (2009) reported significant bi-directional associations between short night time sleep duration and hyperactivity trajectories across early childhood. Steinsbekk and Wichstrøm (2015) found that insomnia (DSM-IV criteria) increased risk of developing conduct disorder, major depressive disorder and social phobia, while Attention Deficit Hyperactivity Disorder, Major Depressive Disorder (MDD) and ODD predicted insomnia. As emotional, behavioural and social problems are precursors to (and core features of) youth BPD (Chanen et al 2007b), collectively these studies suggest that sleep problems may be linked to the development of BPD in young populations.…”
mentioning
confidence: 99%